2003
DOI: 10.1097/00061198-200302000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocystinemia in Pseudoexfoliation Glaucoma

Abstract: Hyperhomocystinemia may be associated with pseudoexfoliation glaucoma, which may partially explain the increased risk of vascular diseases among patients with pseudoexfoliation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 25 publications
5
51
0
8
Order By: Relevance
“…Coffee consumption has been shown to increase plasma homocysteine (Hcy) levels in several randomized clinical trials. [18][19][20] Hcy levels in plasma, [21][22][23][24][25][26] aqueous humor, 27 and tear fluid 28 are consistently elevated in ES patients compared to those in control subjects. Elevated Hcy may enhance exfoliation material formation by contributing to vascular damage, 29 oxidative stress, 30,31 and extracellular matrix alterations.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Coffee consumption has been shown to increase plasma homocysteine (Hcy) levels in several randomized clinical trials. [18][19][20] Hcy levels in plasma, [21][22][23][24][25][26] aqueous humor, 27 and tear fluid 28 are consistently elevated in ES patients compared to those in control subjects. Elevated Hcy may enhance exfoliation material formation by contributing to vascular damage, 29 oxidative stress, 30,31 and extracellular matrix alterations.…”
Section: Resultsmentioning
confidence: 91%
“…Several studies show that Hcy levels are elevated in blood, aqueous humor, and tears taken from ES patients compared to those in controls. [21][22][23][24][25][26][27][28] Elevated Hcy levels, in turn, may contribute to vascular leakage and dysfunctional extracellular matrix remodeling in ES. 54 Alternatively, elevated Hcy levels are a consequence and not a cause of ES, and some unlinked factor(s) related to heavy coffee consumption may contribute to EG/EGS.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinaemia, which is a major risk factor for vascular diseases (including venous thrombosis), was reported to be more common in XFS and XFG patients than in healthy controls in several studies. [39][40][41][42] Finally, endothelin-1, which is a potent vasoconstrictor, seems to be significantly increased in the aqueous of XFS eyes, which could contribute to the obliterative vasculopathy. 43 Elevated IOP and glaucoma have also been suggested as a cause for the association of XFS with CRVO.…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma homocysteine has been reported in pseudo-exfoliative 17,18 but not in primary angle glaucoma. 19 Studies have shown increased plasma homocysteine in patients with age-related macular degeneration.…”
Section: Diabetic Retinopathymentioning
confidence: 95%